Management of Indonesia’s boat people - Yuniarti; Pasan, Etha; Retnowatik, Frentika Wahyu; Wirawan, Rendy (Universitas Djuanda Bogor, 2024)
International migration in the case of boat people in Berau Waters is one of the problems faced by Indonesia Government over times. Their cross border activities of three countries between Philippine, Malaysia and Indonesia had an impact on Indonesia’s economics, social, politics and environment, especially Berau. This study aims to explain the efforts of the Government of Indonesia in boat people management in Berau Regency. The result shows that the government used a normative approach based on Undang-Undang No.6/2011 concerning immigration and a humanitarian approach involved local government agencies and communities. Such efforts had been able to decrease the number of boat people migrating to Berau Waters from 2010-2020